2022
DOI: 10.3390/agriculture12030408
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization of Newly Developed Self-Propelled Variable Height Crop Sprayer Using Response Surface Methodology (RSM) Approach

Abstract: The number of spray deposits plays an important role in effective and efficient spraying. The spraying equipment is one of the most significant factors that affect the number of spray deposits. Therefore, the study was focused on the parameter optimization of a newly developed self-propelled variable height crop sprayer. Response surface methodology (RSM) along with Box–Behnken design (BBD) was used to study the effect of the independent variables (forward speed, spray height, and spray pressure) on response v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…stated that the application of high mixture volumes makes it impossible to determine droplet density since several water-sensitive labels are completely taken over by a single stain, which can be explained by the combination of several drops. Thus, in view of the results found in this study, corroborating the aforementioned authors, it appears that water-sensitive paper is more suitable for verifying target coverage and inadequate for evaluating the population of droplets Khah et al (2022). recommend a density of 30 to 40 drops cm -2 for systemic insecticides.…”
supporting
confidence: 82%
“…stated that the application of high mixture volumes makes it impossible to determine droplet density since several water-sensitive labels are completely taken over by a single stain, which can be explained by the combination of several drops. Thus, in view of the results found in this study, corroborating the aforementioned authors, it appears that water-sensitive paper is more suitable for verifying target coverage and inadequate for evaluating the population of droplets Khah et al (2022). recommend a density of 30 to 40 drops cm -2 for systemic insecticides.…”
supporting
confidence: 82%
“…It is concluded that as the value of pressure increased, the value of droplet density also increased. Khan et al [39] reported the same trend. Figure 11c showed that the change in the droplet density was very little or less than 1% in treatments T10 and T18 when both height and pressure increased at the same time at a constant speed of 6 km h −1 .…”
Section: Effect Of Spray Treatments On Droplet Density Of Sprayersupporting
confidence: 53%
“…Carroll [38] reported that as forward speed increased, the droplet density decreased. Khan et al [39] also reported that the droplet density decreases as forward speed and spray height increase. Figure 11b showed that in treatment T4 (4 km h −1 , 55 cm, and 3 bar) and T6 (4 km h −1 , 55 cm, and 7 bar) when pressure increased (3 bar to 7 bar), the value of droplet density was increased up to 7.1%.…”
Section: Effect Of Spray Treatments On Droplet Density Of Sprayermentioning
confidence: 92%
See 2 more Smart Citations